The Description of the Application of Healthy Workplaces at PT PJB Power Plant Unit Gresik - Dinda Ocvita Windi Pratiwi (The Indonesian Journal of Occupational Safety and Health, 2020)
Introduction: Healthy workplaces is a concept where everyone in the work environment works together to achieve the vision of the health and welfare of workers and the surrounding community. PT PJB UP Gresik is a supplier of electrical energy since 14th June 1996, and has received top management awards in 2018 with zero accidents in 2018 and 2019. This study aimed to describe the working environment of PT PJB UP Gresik using Healthy Workplaces Theory. Methods: The study was conducted in February-August 2019 through descriptive of quantitative method. The population involved was 325 workers selected using simple random sampling, divided into two groups of 22 managements, and 76 staffs. Research tool used was in the form of WHO questionnaire. The study passed the ethical review of the Faculty of Dentistry, Universitas Airlangga in June 2019 number 324/HRECC.FODM/VI/2019. Result: As much as 97% of the management and 76% of staff agreed that the company had health-oriented regulations. It also obtained that 100% management, and 92% staff agreed that the company's psychosocial environment was healthy. As much as 96% of each respondent group agreed that the work environment was safe. About 63% management and 64% staff agreed that the company supported changes in healthy lifestyles. Around 60% management and 64% staff agreed that the company's health service units were available and implemented well. The statement of company being a good effect has been approved by 89% of the management. Conclusion: PT PJB UP Gresik has a healthy work environment and can be improved if it pays more attention to the lifestyle and the functions of health service.Keywords: heat radiation, noise, ship production